Synthesis and Characterization of Physically Mixed V2O5.CaO as Bifunctional Catalyst for Methyl Ester Production from Waste Cooking Oil - Mulyatun Mulyatun; Istadi Istadi; Widayat Widayat (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Synthesis of the solid bifunctional vanadium-calcium mixed oxides catalyst was accomplished by application of a simple physical mixing approach. In this work, we compared the catalytic activity of CaO and 2%V2O5.CaO catalyst. Various characterization methods, such as X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier transform infrared (FTIR), BET surface area, and temperature-programmed desorption (TPD) of CO2 and NH3, were involved in studying the newly synthesized catalysts. The presence of CaO, CaCO3, and Ca(OH)2 compounds in the synthesized catalyst were detected by XRD and FTIR analysis. The existence of 2% V2O5 on the CaO catalyst surface was demonstrated by XRF analysis. From TPD-NH3, TPD-CO2, and BET surface area analysis, it was known that the 2% V2O5-CaO catalyst had a higher total number of acid-base sites and surface area than the CaO catalyst. In the fatty acid methyl esters (FAME) production from waste cooking oil (WCO) with higher free fatty acid (FFA), CaO could only catalyze the transesterification reaction. In contrast, 2%V2O5-CaO could successfully catalyze both the esterification of FFA and the transesterification of triglyceride (TG) simultaneously in a one-step reaction process. Thus, these results prove that 2%V2O5.CaO can act as a bifunctional catalyst in the production of biodiesel from WCO. Moreover, the synthesized 2%V2O5.CaO catalyst could achieve a maximum FAME yield of 51.30% under mild reaction conditions, including a 20:1 methanol to oil molar ratio, 60 °C reaction temperature, 1 wt% of catalyst loading, and 3 hours of reaction time.